The Effectiveness of Expressive Writing Therapy in Reducing Anxiety in Children Victims of Bullying at SMP Negeri 1 Mojotengah Wonosobo in 2021 - Sekar Lakshmi Prameswari; Reni Mareta; Septi Wardani (Urecol Journal. Part D: Applied Sciences, 2022)
Expressive writing therapy is the one of therapy which use writing to reflect cognition and depth affection about traumatic or unpleasant experience. Expressive writing therapy is carried out with psychotherapy or other counseling approaches that can be done individually and in groups. This research is aimed to investigate the effectiveness of expressive writing therapy in order to reduce anxiety in children who are victims of bullying. The method used is an experiment reseatch which uses Pretest Posttest Control Group design with 46 subjects participated by using Purposive Sampling. The normality of data was used with Mann-Whitney U-Test test using IBM statistics 21 for windows. Data were collected using anxiety scale from Hamilton Rating Scale For Anxiety (HARS). The results of Mann-Whitney U-Test show a result with Asymp. Sig (2-tailed) 0,002 (p< 0,05) which proves the effectiveness of expressive writing therapy in order to minimizing anxiety on the bully-victims all students in junior high school in Mojotengah.